(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the prevalence of anemia, bone marrow response through reticulocyte count, and factors influencing these among pregnant women undergoing testing at HANHPHUCLAB Medical Diagnostic Center in 2024. Method: A cross-sectional descriptive study was conducted on 180 pregnant women at HANHPHUCLAB from March to May 2024. Blood samples were collected from the pregnant women for Hb and reticulocyte count testing. Results: 180 pregnant women met the study criteria, with an anemia prevalence of 11.7% and predominantly microcytic hypochromic anemia at 23.8%. Among pregnant women, 9.5% of anemic pregnant women and 11.3% of non-anemic pregnant women showed increased reticulocyte counts. The study found a statistically significant association between anemia and gestational weeks. Conclusion: Pregnant women from 6 to 16 weeks of gestation require assessment for anemia and bone marrow response to plan support, counseling, and treatment for anemia during pregnancy.